Prevalence and factors associated with failed induction of labor in Worabe Comprehensive Specialized Hospital, Southern Ethiopia - Mohammed, Muhdin; Oumer, Rewda; Mohammed, Fatuma; Walle, Fantahun; Mosa, Hassen; Ahmed, Ritbano; Eanga, Shamill (PLOS ONE, 2022)
Background Induction of labor is one of the most used obstetric procedures in the world. It is performed in around 20% of all pregnancies. Failed induction of labor, on the other hand, has been associated with poorer mother and newborn health outcomes. Besides, there is a scarcity of data on the current burden and drivers. Therefore, this study aimed to assess the prevalence and factors associated with failed induction in Worabe Comprehensive Specialized Hospital, Southern Ethiopia. Methods A retrospective cross-sectional study was conducted on medical records of mothers who delivered through induction of labor during September 1st, 2018 to August 30th, 2020. The samples were collected using a systematic sampling technique. The data was extracted using a checklist. Data were entered into EpiData (version 3.1) and analyzed using SPSS (version 24). Multivariable logistic regression analyses were used to decide the association of explanatory variables with the outcome variable. Odds ratio with their 95% CI were calculated to identify the presence and strength of an association. A p-value of < 0.05 was used to declare statistical significance. Results In this study, the prevalence of failed induction was observed to be 22.2%. The associated factors included rural residence (AOR = 5.7, 95% CI: 3.12–11.02), primiparity (AOR = 8.4, 95% CI: 2.72–22.36) and unfavourable bishop score (AOR = 5.9, 95% CI: 4.52–16.12). Conclusions In comparison to the rate reported in developed countries, the study area had a high rate of failed induction. Being rural residence, primiparity and unfavourable bishop score were the associated factors of failed induction. Therefore, to reduce of the rate of failed induction, health care practitioners should analyze cervical status (using Bishop Score) to decide the possibility of successful induction, with a focus on associated factors like parity.